Soil Health and Nutrient Density: Beyond Organic vs. Conventional Farming - Montgomery, David R.; Biklé, Anne (Frontiers in Sustainable Food Systems, 2021)
Controversy has long surrounded the question of nutritional differences between crops grown organically or using now-conventional methods, with studies dating back to the 1940s showed that farming methods can affect the nutrient density of crops. More recent studies have shown how reliance on tillage and synthetic nitrogen fertilizers influence soil life, and thereby soil health, in ways that can reduce mineral micronutrient uptake by and phytochemical production in crops. While organic farming tends to enhance soil health and conventional practices degrade it, relying on tillage for weed control on both organic and conventional farms degrades soil organic matter and can disrupt soil life in ways that reduce crop mineral uptake and phytochemical production. Conversely, microbial inoculants and compost and mulch that build soil organic matter can increase crop micronutrient and phytochemical content on both conventional and organic farms. Hence, agronomic effects on nutritional profiles do not fall out simply along the conventional versus organic distinction, making the effects of farming practices on soil health a better lens for assessing their influence on nutrient density. A review of previous studies and meta-studies finds little evidence for significant differences in crop macronutrient levels between organic and conventional farming practices, as well as substantial evidence for the influence of different cultivars and farming practices on micronutrient concentrations. More consistent differences between organic and conventional crops include that conventional crops contain greater pesticide levels, whereas organically grown crops contain higher levels of phytochemicals shown to exhibit health-protective antioxidant and anti-inflammatory properties. Thus, part of the long-running controversy over nutritional differences between organic and conventional crops appears to arise from different definitions of what constitutes a nutrient—the conventional definition of dietary constituents necessary for growth and survival, or a broader one that also encompasses compounds beneficial for maintenance of health and prevention of chronic disease. For assessing the effects of farming practices on nutrient density soil health offers an enhanced perspective on the provisioning of micronutrients and phytochemicals that support human health.